(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
As the tidal stream energy sector develops, reducing the Levelised Cost of Energy (LCOE) is essential to sustain commercialisation. Modular multi-rotor foundations, with bi-directional turbines, reduce offshore operational complexity through smaller turbine diameters and lift weight, in turn reducing the device Operational Expenditure (OpEx). With the introduction of modular, multi-rotor foundations, the wake-induced impacts that these structures have on turbine performance must be investigated to better estimate energy yield, loading, and fatigue life. This study sets the scene for investigating the relationship between the turbulent wake generated by a modular ballast weighted foundation and 2-bladed Horizontal Axis Tidal Turbine (HATT) motivated by the HydroWing multi-rotor device concept. The presented work aims to determine the broader magnitude and severity of the loads and establish a robust methodology to be followed with further high-fidelity modelling. Initially, a transient RANS Computational Fluid Dynamics (CFD) simulations environment with a sliding mesh is configured and validated against experimental data. A turbine in free-stream isolation is simulated as a benchmark case with the modular foundation sequentially introduced to analyse the impact of the structure. Key findings suggest that operating turbines downstream of the multi-rotor foundation could cause a 20% fluctuation in thrust loading at a 1.82 Hz frequency resulting in a mean Cp reduction of 8% over a revolution.